Fostering Speaking Confidence in Indonesian EFL Learners: Teaching Strategies at Cambridge English School - Sulistiana Ulpa; Muhammad Tahir; Fatimah Hidayahni Amin (International Journal of Language, Education, and Literature, 2025)
Speaking confidence is a crucial factor in successful English language learning, particularly in EFL settings where anxiety and low self-esteem often hinder oral participation. This qualitative study investigates the teaching strategies employed by English teachers at Cambridge English School, a private language institution in Makassar, Indonesia, to foster students’ confidence in speaking. Utilizing classroom observations and in-depth interviews with three experienced teachers, the study applies Braun and Clarke’s thematic analysis to identify six key strategies: reflective questioning, warm-up activities, use of relevant and authentic topics, mixed-ability group work, prioritizing fluency over accuracy, and encouraging feedback. Findings reveal that mixed-ability groupings serve as a vital mechanism for peer scaffolding and emotional support, consistent with socio-constructivist and social cognitive theories. Other strategies contribute to creating a psychologically safe and motivating environment that enhances students’ willingness to communicate. The study underscores the importance of learner-centered practices that integrate cognitive and affective dimensions to build speaking confidence. Implications for EFL teaching and teacher training include deliberate group composition and fluency-focused instruction to foster risk-taking and spontaneous speech. This research bridges theory and practice, offering practical insights for educators aiming to cultivate oral confidence in diverse EFL classrooms.